Republic of Senegal Social Protection Public Expenditure Review, 2010-2015 : Analytical Report - Rougeaux, Solène (World Bank, Washington, DC, 2017)
This summary presents the five key conclusions and recommendations that flow from the analytical report of the social protection public expenditure review. The review focuses on Senegal social protection programs between 2010 and 2015